A new black fly species of Simulium (Gomphostilbia) (Diptera: Simuliidae) from Sulawesi, Indonesia - Takaoka, Hiroyuki; Sofian-Azirun, Mohd; Chen, Chee Dhang; Halim, Muhammad Rasul Abdullah; Lau, Koon Weng; Low, van Lun; Suana, I. Wayan (Zootaxa, 2019)
Simulium (Gomphostilbia) marosense sp. nov. is described based on adults, pupae and mature larvae from Sulawesi, Indonesia. This new species is placed in the Simulium duolongum subgroup of the S. batoense species-group, representing the ninth member for the subgroup in Sulawesi. This new species is characterized by a narrow female frons and pupal gill with eight filaments, of which two filaments of the ventral pair are 1.9–3.0 times as long as the six other filaments. Taxonomic notes are provided to distinguish this new species from related species.